From Conflict to Solidarity: Revisiting Muslim-Christian Relation after 171 Tragedy in Mataram - Ahdar, Rozi (LP2M UIN Sunan Kalijaga, 2023)
Several Muslim-Christian conflicts occurred after the regime of Soeharto ended. Two of them are the Maluku and Poso conflicts. Another one occurred in 2000, on January 17th, or what is well known as the 171 tragedy. Why did the 171 tragedy occur in Lombok? Extremism and puritanism could be the answers. It is a sect that exists in both Islam and Christianity that “justifies” violence in the name of religion. What is interesting about the 171 tragedy is that it was not continued for long-term periods. Soon after the condition is safe, economic and academic collaboration between Islam and Christianity will resume normally. This is a descriptive-qualitative paper. This paper argues that 171 tragedy is the beginning of Islam-Christian collaboration to fight extremism in religion instead of an enmity reason for both religions. With that understanding, it is hoped that solidarity to combat extremism will continue to grow. The occurrence of 171 tragedies caused chaos and detriment for Christians. However, it transformed Mataram from a city of religious contestation among Islam, Christianity, Hinduism, and Buddhism into a city of unity. [Sejumlah konflik antara Muslim dan Kristen muncul setelah jatuhnya rezim Soeharto. Salah duanya terjadi di Maluku dan Poso. Konflik lain terjadi pada 17 Januari tahun 2000 atau dikenal dengan tragedi 171. Kenapa kemudian tragedi 171 terjadi di Lombok? Ekstremisme dan puritanisme bisa menjadi jawaban. Ini merupakan sebuah sekte di Islam maupun Kristen yang “menghalalkan” kekerasan dengan dalil agama. Yang menarik dari tragedi 171 adalah, ia tidak berlangsung dalam periode panjang. Tidak lama setelah konflik mereda, kolaborasi ekonomi serta bidang akademis antara Muslim dan Kristen kembali normal. Ini adalah penelitian deskriptif-kualitatif. Argumen utamanya adalah, bahwa tragedi 171, alih-alih menjadi alasan permusuhan Islam-Kristen, ia justru menjadi awal solidaritas kedua agama untuk melawan ekstremisme. Dengan pemahaman tersebut, diharapkan kerja sama untuk melawaan ekstremisme terus tumbuh. Terjadinya tragedi 171 tentu menyebabkan kekacauan dan kerugian bagi umat Kristen. Di sisi lain, tragedi tersebut telah mentransformasi Mataram dari sebuah kota yang menjadi tempat kontestasi Islam, Kristen dan Hindu, menjadi kota persatuan.]